Foreign capital and Finland: central government's firstperiod of reliance on international financial markets 1862-1938 - Mika Arola (Bank of Finland, 2006)
The main objective of the study is to evaluate the Finnish central government's foreign borrowing between the years 1862 and 1938. Most of this period was characterised by deep capital market integration that bears resemblance to the liberal world financial order at the turn of the millennium.The main aim is to analyse the credit risk associated with the state and its determination by evaluating the world financial market centres' perception of Finland.By doing this, the study is also expected to provide an additional dimension to Finland's political and economic history by incorporating into the research the assessments of international capital markets regarding Finland during a period that witnessed profound political and economic changes in Finnish society.The evaluation of the credit risk mainly relies on exchange-rate risk free time series of the state's foreign bonds.They have been collected from quotations in the stock exchanges in Helsinki, Hamburg, Paris and London.In addition, it investigates Finland's exposure to short-term debt and Moody's credit ratings assigned to Finland.The study emphasises the importance of the political risk. It suggests that the hey-day of the state's reliance on foreign capital markets took place during last few decades of the 19th century when Finland enjoyed a wide autonomy in the Russian Empire and prudently managed its economy, highlighted in Finland's adherence to the international gold standard.Political confrontations in Finland and, in particular, in Russia and the turbulence of the world financial system prevented the return of this beneficial position again.Through its issuance of foreign bonds the state was able to import substantial amounts of foreign capital, which was sorely needed to foster economic development in Finland.Moreover, the study argues that the state's presence in the western capital markets not only had economic benefits, but it also increased the international awareness of Finland's distinct and separate status in the Russian Empire and later underlined its position as an independent republic.
URN:NBN:fi:bof-201408071697
Keywords: E65; G15; H63; N13; 330; credit risk; government borrowing; financial market; government bonds; state finances; Internationale Staatsschulden; Kreditrisiko; Öffentliche Anleihe; Internationaler Finanzmarkt; Finnland